Observing Dynamical Processes in Multiplex Networks by Using Edge Correlation - Bogojeska, Aleksandra; Filiposka, Sonja; Mishkovski, Igor; Kocarev, Ljupcho (My University, 2013)
The recent emergence of the new representation of interconnected layers of networks, called multiplex networks, refocused the research in complex networks. The analysis of these networks requires redefinition of the dynamical processes and topological properties present in one-layered graphs. The main focus in this work is the relation between consensus and synchronization defined on multiplex graphs and edge correlation of the graph layers. We show numerically that the information of edge correlation between layers offers substantial insights in the complex multiplex structure, thus, contributing to simplified and faster analysis and design of multiplex graphs with desired consensus or synchronization properties.
Keywords: multiplex networks, consensus, synchronization, edge overlap, correlation